Journal of Special Education and Rehabilitation from Scientific Periphery to Relevant Scientific Journal - Trajkovski, Vladimir (Journal of Special Education and Rehabilitation, 2015)
This editorial describes the growth of the Journal of Special Education and Rehabilitation in the last 18 years since it began to be published. Although it began as a local and specialized, it managed to develop into an international and scientific and to attract a large number of authors from over 30 countries around the world. Currently, the journal is indexed in 65 databases worldwide. Macedonia is a tough periphery in the world of science. But, this does not prevent the journal to become more visible and significant in scientific areas that the field of special education and rehabilitation covers. In our country there are many factors that hinder the way for the creation of high quality scientific journal. These are discussed in detail in the paper. To reach higher relevance of the journal, a great dedication of the people working in the publish-ing offices is necessary. The editors of small journals of the region need to exchange their experiences. The editorial teams of smaller journals have to gather experi-ence from major journals. They need to put more effort into increasing the visibility of the journal online, and they can do this by sharing the labor of the social media. The competent Ministry of Education and Science should allo-cate a greater percentage of the gross domestic product for publishing as small journals could become more relevant in the world of science. The conclusion is that small journals may con-tribute in the world of science with relevant scientific information.
ДЕФЕКТОЛОШКА ТЕОРИЈА И ПРАКТИКА ОД НАУЧНАТА ПЕРИФЕРИЈА ДО РЕЛЕВАНТНО НАУЧНО СПИСАНИЕ
Keywords: Journal of Special Education and Rehabilitation, scientific periphery, scientific journal, quality of journal